2008
DOI: 10.1037/0278-6133.27.1.100
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal responses among sibling dyads tested for BRCA1/BRCA2 gene mutations.

Abstract: Objective-The familial context plays an important role in psychosocial responses to genetic testing. The purpose of this study was to compare sibling pairs with different combinations of BRCA1/BRCA2 test results on measures of affect, interpersonal responses, and physiological reactions.Design-Forty-nine sibling dyads with different combinations of BRCA1/BRCA2 test results (i.e., mixed, positive, negative) completed a questionnaire, and 35 of the dyads also participated in a laboratory-based discussion of gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 46 publications
(59 reference statements)
3
17
0
Order By: Relevance
“…In this study, some participants described being the sole sibling who turned out to be mutation positive, followed by lack of interest from the siblings who turned out to be mutation negative. Hamann et al (2008) report that siblings who received discordant results perceived their siblings as less friendly and less supportive compared to those who received identical test results.…”
Section: Discussionmentioning
confidence: 90%
“…In this study, some participants described being the sole sibling who turned out to be mutation positive, followed by lack of interest from the siblings who turned out to be mutation negative. Hamann et al (2008) report that siblings who received discordant results perceived their siblings as less friendly and less supportive compared to those who received identical test results.…”
Section: Discussionmentioning
confidence: 90%
“…This was further corroborated in the literature in cases of Huntington's disease, 3 HIV/AIDS, 4 as well as cancer genetics. [5][6][7] Beyond familial relationships, survivor guilt has also been identified in social relationships, such as individual guilt for testing negative for a genetic test whereas other members of a support group tested positive. 8 As such, in both familial and social scenarios, the individuals who tested negative felt tremendous guilt over being "spared" and therefore surviving.…”
mentioning
confidence: 98%
“…The structural validity of the 'abetting' dimension items may be both context (e.g., intrateam) and relationship (e.g., teammates) specific. Research examining interper sonal support actions found that more similar individuals reported more communal behaviors and suggested that those who differed may experience more tension and distance (Hamann et al, 2008). Similarly, individuals who view themselves and others similarly express stron ger communal values (Locke & Christensen, 2007).…”
Section: Discussionmentioning
confidence: 97%